Bloodwork: Circulatory Disorders, Immunity, and the Scarring of Systems. (7th November 2022) - Yates‐Doerr, Emily
Abstract: In June 2021, laboratory analysis of my blood indicated dangerously low levels of iron. This article chronicles my subsequent diagnosis of uterine fibroids, the hysterectomy that followed, and the scarring that came afterward. In doing so, the article tells the story of how blood circulates—or not—through biosocial systems. It shows how the properties of blood are frequently connected to conditions of exploitation to advance the argument that paying attention to how blood works, or "bloodwork, " can illuminate systemic inequality and alternative systems. In conversation with social reproduction theory, I consider capitalism's powerful extractivist orderings of immunity in which my iron comes at another's expense, alongside logics of immunity based on different circulatory visions. I hold on to the possibility of growing stronger without weakening others—so long as we can attend to history and its scars.